Psychometric properties of the Chinese version of Sport Anxiety Scale-2 - Zhang, Jinrui; Zhang, Zhiwen; Peng, Shuo; Veloo, Arsaythamby; Bailey, Richard Peter; Tan, Wee Hoe (Frontiers in Psychology, 2023)
Introduction The Sport Anxiety Scale-2 (SAS-2) is a validated measure of sports trait anxiety, with promising psychometric properties. However, its cross-cultural applicability in Chinese samples remains unexplored. Thus, the primary objectives of this study were twofold: to translate the SAS-2 into Chinese and assess the psychometric properties of the Chinese version. Methods In Study 1, we initiated the translation of the SAS-2 into Chinese. This assessment involved bilingual Chinese students proficient in both English and Chinese. Additionally, we conducted a cross-linguistic measurement invariance analysis. In Study 2, we delved into the psychometric properties of the Chinese SAS-2 using a sample of Chinese student athletes. This examination encompassed an evaluation of its factor structure, convergent and discriminant validity, and measurement invariance across genders. Results Our findings in Study 1 indicated no significant differences in item scores between the Chinese SAS-2 and the English version, and measurement invariance across languages. In Study 2, we uncovered that the Chinese SAS-2 and its factors exhibited excellent reliability, with Cronbach’s alpha values exceeding 0.80. Confirmatory factor analyses upheld the original three-factor model, demonstrating acceptable model fit indices (CFI = 0.96, TLI = 0.93, RMSEA = 0.08). Furthermore, all three factors of the Chinese SAS-2 displayed significant and positive correlations with athlete burnout and State-Trait anxiety. Additionally, this study elucidated the mediating role of Concentration Disruption (Somatic anxiety and Concentration Disruption) in the relationship between the Trait (State) anxiety, and athlete burnout. Moreover, we identified measurement invariance of the Chinese version of the SAS-2 across genders. Finally, female college athletes exhibited significantly higher scores in somatic anxiety and worry compared to their male counterparts. Discussion In sum, our findings affirm that the Chinese version of the SAS-2 demonstrates robust reliability and correlates effectively with related criteria, thus validating its suitability for use in a Chinese context.